Demonstration of Software-Reconfigurable Real-Time FEC-Enabled 4/16/64-QAM-OFDM Signal Transmission in an X-Band RoF System - Ming Chen; Xin Xiao; Jianjun Yu; Fan Li; Zhao Rena Huang; Hui Zhou (IEEE Photonics Journal)
In this paper, to the best of our knowledge, this is the first time that the generation and reception of online software-reconfigurable real-time 4/16/64-quadrature amplitude modulation (QAM)-encoded and forward error correction (FEC)-enabled orthogonal frequency-division multiplexing (OFDM) signals over X-band fiber-over-radio-based upstream links has been demonstrated. A Reed–Solomon code, i.e., RS (288, 256), with symbol interleaving/deinterleaving is applied to enhance bit-error-rate (BER) performance. The experimental results show that the 4/16/64-QAM-OFDM signals with net data rates of 1.6/3.2/4.8-Gb/s after 1.5-m wireless and 2.26-km SMF-28 transmission with BERs below the hard-decision FEC threshold of 3.8e-3 can be successfully achieved without using FEC. With the help of symbol-interleaved RS code, a post-FEC BER below 1e-8 can be observed when the pre-FEC BER is around 1e-3.